Doping dependent transport in YBCO nanostructures: insights into the microscopic mechanism for high critical temperature superconductivity - Toskovic, Ranko (My University, 2020)
The microscopic mechanism responsible for superconductivity in high critical temperature superconductors (HTSs), almost three decades after their discovery, still remains unknown. It is widely believed that studies in the underdoped (UD) regime of these materials could shed light on this unresolved question. In this thesis project, a controllable and reproducible Pulsed Laser Deposition (PLD) growth of underdoped YBa2Cu3O7-δ (YBCO) films was done by changing only the postannealing pressure. X ray diffractometry (XRD) scans of the films have shown a continuous YBCO unit cell expansion as the pressure decreased, indicating a reduction in the doping level of our films. Rather sharp resistance vs. temperature transitions obtained in our films indicate a high level of homogeneity. First steps towards optimization of the surface properties of the films have been also undertaken. A soft-patterning technique developed previously in our group, preserving homogeneity of submicron structures, was employed for nanorings’ patterning on the optimally doped films. Little Parks (LP) experiments were conducted on rings with different sizes. Cooper pairs have been identified as the predominant charge carriers in all the rings, as expected at the optimal doping level.
Keywords: high critical temperature superconductivity, YBCO, Little Parks effect, underdoped and optimally doped films, nanorings